Descemet’s stripping automated endothelial keratoplasty: The relationship between postoperative central corneal thickness and the requirement for re-bubbling - Brok Molbech Madsen, Morten; Ivarsen, Anders; Østergaard Hjortdal, Jesper (Journal of EuCornea, 2020)
To investigate whether central corneal thickness (CCT) at the first postoperative day was predictive of partial or complete graft detachment requiring re-bubbling. We conducted a retrospective registry-based study including 943 DSAEK procedures. Included subjects were divided into 2 subgroups depending on the postoperative need for re-bubbling. Using the electronic patient record system at the Department of Ophthalmology, Aarhus University Hospital, we gathered information on CCT measured using optical pachymetry on the first postoperative day, subject characteristics as well as the need for postoperative re-bubbling. Prior to our data collection we hypothesized that increased CCT at the first postoperative examination was predictive of later re-bubbling. Postoperative CCT in the re-bubble group was 854 µm (CI: 836–871, N = 107) which was significantly higher than postoperative CCT of 787 µm (CI: 782; 793, N = 836) in the no-re-bubble group (P < 0.001). Further, a Receiver Operating Characteristics (ROC)-curve was created. Our data revealed a sensitivity of 71.0% and specificity of 63.3% for re-bubbling using a cut-off value of 810 µm. CCT on the first postoperative day can to some extend predict the need for postoperative re-bubbling and in this way identify eyes at risk of graft detachment requiring intervention.